1991
DOI: 10.1079/bjn19910008
|View full text |Cite
|
Sign up to set email alerts
|

Transport of feed selenium to different tissues of bulls

Abstract: The effects of different types of Se supplementation on the selenium concentration of beef, bovine internal organs and some other tissues were studied. The animals (thirty-two bulls) were kept in four dietary groups from birth until to the age of 13-14 months, and fed on rations containing either 0.03 mg Se/kg (basic level in local feeds), 0.25 mg inorganic Se supplemented as sodium selenite, or 0.25 or 0.4 mg/kg plant Se in dry matter from feed produced by spraying with sodium selenite. Samples of four muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
3
13
0
4
Order By: Relevance
“…Metabolismo, exigências e excreção de selênio Após a absorção intestinal, SeMet e SeCis podem ser metabolizadas pelos animais como aminoácidos (EKHOLM et al, 1991). Isso ocorre especialmente com a SeMet, que, de forma similar à metionina, pode ser incorporada a proteínas pelo mesmo códon AUG, pois o tRNA não diferencia a metionina da SeMet.…”
Section: Selênio Nos Alimentosunclassified
“…Metabolismo, exigências e excreção de selênio Após a absorção intestinal, SeMet e SeCis podem ser metabolizadas pelos animais como aminoácidos (EKHOLM et al, 1991). Isso ocorre especialmente com a SeMet, que, de forma similar à metionina, pode ser incorporada a proteínas pelo mesmo códon AUG, pois o tRNA não diferencia a metionina da SeMet.…”
Section: Selênio Nos Alimentosunclassified
“…Fertilizers used for the production of hay and fodder were supplemented with 6 mgakg of Se in the form of sodium selenate, and fertilizers for cereal were supplemented with 16 mgakg. As a result, Se content increased in agricultural products, in dairy products and in meat (Varo et al, 1988;1994;Eurola et al, 1989Eurola et al, , 1991Ekholm et al, 1991). An increase followed in the Se intake and resulted in higher serum Se concentration in the whole population.…”
Section: Introductionmentioning
confidence: 99%
“…The Se content in both muscles increased 2.75 times when compared with the control. Several authors observed significant effects of supplementation with organic Se on the Se level in cattle muscles (Ekholm et al 1991;Lawler et al 2004;Juniper et al 2008;Pereira et al 2012). The significance of the enrichment is different depending on the Se type, source and administered dose.…”
Section: Chemical Composition Of Meatmentioning
confidence: 99%